2009
DOI: 10.1021/jp909232b
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Spectral, Electrochemical, and Photovoltaic Properties of Acene-Modified Zinc Porphyrins

Abstract: A series of acene-modified zinc porphyrins (benzene to pentacene, denoted as LAC-1 to LAC-5) were prepared to study their absorption spectra, electrochemical properties, and photovoltaic properties. For the absorption spectral changes in THF, porphyrin B bands are red-shifted and broadened from 449 to 501 nm for LAC-1 to LAC-3, showing the effect of additional π-conjugation. In contrast, the B bands of LAC-4 and LAC-5 are blue-shifted. In addition, the tetracenyl group of LAC-4 gives rise to absorption bands i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 29 publications
4
92
1
Order By: Relevance
“…Similar to our findings, the HOMO and LUMO patterns of their acene-modified zinc porphyrin dyes demonstrate increasing localization on the tetracenyl and pentacenyl groups for LAC4 and LAC5. [23] The increasing localization of p orbitals at tetracenyl and pentacenyl units might also affect the fluorescence emission of TPA-AC4 and TPA-AC5, since electronic localization in the tetracenyl and pentacenyl moieties may enable intersystem crossing and internal conversion to become the main channels of deactivation, [23] as discussed later.…”
Section: Molecular Orbital Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our findings, the HOMO and LUMO patterns of their acene-modified zinc porphyrin dyes demonstrate increasing localization on the tetracenyl and pentacenyl groups for LAC4 and LAC5. [23] The increasing localization of p orbitals at tetracenyl and pentacenyl units might also affect the fluorescence emission of TPA-AC4 and TPA-AC5, since electronic localization in the tetracenyl and pentacenyl moieties may enable intersystem crossing and internal conversion to become the main channels of deactivation, [23] as discussed later.…”
Section: Molecular Orbital Patternsmentioning
confidence: 99%
“…Acenes are polycyclic aromatic hydrocarbons consisting of linearly fused benzene rings with big p conjugations, and acene compounds such as anthracene are expected to be beneficial to red-shift the absorption spectra. [23][24][25] Lin et al have reported a series of acene-modified zinc porphyrins (benzene to pentacene) and investigated their absorption spectra, electrochemical properties, and photovoltaic properties. For the performance of the DSSCs, the overall efficiencies first increase then decrease, and the introduction of anthracene shows the highest efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] So far, a large number of porphyrins have been developed as sensitizers for DSSCs such as carboxyphenyl metalloporphyrins (h = 0.2-3.6 %); [10] thiophene-, olefin-, and acetylene-linked porphyrins (h = 3.6-5.1 %); [11] quinoxaline-fused porphyrins (h = 5.2-6.5 %); [12] zinc-zinc porphyrin dimers (h = 2.1-5.5 %); [13] bacteriochlorin (h = 1.1-6.6 %); [14] 2,4-pentadienoic acid bpyrrolic-functionalized porphyrins (h = 3.03-7.47 %); [15] phenylethynyl-substituted porphyrins (h = 0.25-6.12 %); [16] meso-(diarylamino)-substituted porphyrins (h = 3.8-13 %); [7,17] 4-ethynylstyryl b-pyrrolic-functionalized porphyrins (h = 4.3-7.1 %); [18] and acene-modified porphyrins (h = 0.10-5.44 %). [19] The performances of these porphyrins varied depending on the chemical structure. Hence, a further structural modification and improvement of the porphyrinbased dye is still a challenge and needs to be carried out.…”
Section: Introductionmentioning
confidence: 99%
“…On the theory side, oligoacenes have been subject of an intensive debate due to pronounced correlation effects 3,4 . Much of the interest in this class of molecules is driven by organic electronics 5 and photovoltaics 6,7 , where oligoacenes and their derivatives find frequent applications [8][9][10][11][12] . From a broader perspective, a study of systems with linearly fused rings, 'nanographenes', offers means to learn how properties of a molecular wire converge to the one-dimensional limit.…”
mentioning
confidence: 99%